Evaluation of potential tidal impoundment energy systems in Ria de Aveiro, Portugal - Rocha, João (2020)
The shelving of the seabed and funneling of the water by the estuaries is favorable for tidal impoundment technologies. In this work, the estimation of the tidal potential energy for Ria de Aveiro lagoon was achieved through the application of a model developed in the Delft3D software. This software can reproduce the hydrodynamics of this complex system and simulations were run to identify hot spots to retrieve gravitational potential energy. For the selected places, both power and annual energy were calculated. It was concluded that the tidal energy that can be extracted from Ria de Aveiro is considerable, justifying further studies to consider the accommodation of some type of tidal exploitation, in the foreseeable future.